Theoretical and Empirical Insights into Child and Family Poverty: Cross National Perspectives - Fernandez, Elizabeth; Zeʻira, ʻAnat; Vecchiato, Tiziano; Canali, Cinzia (Springer, 2020)
This book brings together a range of theoretical and empirical perspectives on conceptualization, measurement, multidimensional impacts and policy and service responses to address child and family poverty. It illuminates issues and trends through country level chapters, thus shedding light on dynamics of poverty in different jurisdictions. The book is structured into three sections: The first includes introductory chapters canvassing key debates around definition...